Use of Peer Assessment and Self-Assessment in Class Discussions to Assess Concept Understanding Ability of Prospective Biology Educators - Aa Juhanda; Sistiana Windyariani (Magister Pendidikan Biologi, Universitas Negeri Medan, 2021)
The ability of understanding important concepts held by educators and learners. This ability is fundamental in achieving one of the outcomes of learning. Their understanding of the concept of ownership is the ability of a person can use in solving a problem that is related to the concept in everyday life. This descriptive study aims to obtain a description of the conceptual understanding of prospective biology educator students through the use of peer and self-assessment in class discussions. The research subjects were 26 prospective Biology educator students of the 2019/2020 academic year who contracted the human body anatomy physiology course. The instruments used consisted of peer and self assessment sheets, lecturer observation sheets and conceptual understanding questions. Data analysis was carried out quantitatively and qualitatively. The results showed that the average peer assessment score was greater than the self assessment, where the peer assessment was in the moderate category (49%) and the self assessmet was in the poor category (34%). There were only 10 students (38.46%) who were in conformity between peer and self assessment with adequate and insufficient categories. The discrepancy was found in 16 students (61.54%) with the category enough, less and very less. The ability to understand the concept of students on each indicator shows different percentage mean. The highest percentage of concept understanding ability indicators is found in the indicators of explaining the concept with its own sentence structure about something that is read or heard clearly / concretely by 64% (Good), while the lowest percentage of indicators of concept comprehension ability is found in the indicators able to connect symbolic forms (pictures, tables, concept maps, diagrams, graphs, mathematical equations, and other formulas) in concepts with other concepts of 51% (Enough).